Global, regional, and national burden of mental disorders among women of reproductive age, 1990–2021: a systematic analysis of the global burden of disease study 2021 - Cheng, Yifan; Zhao, Yutong; Xu, Ziqing; Wang, Shuaibing; Zhu, Jicun; Yang, Qian; Zou, Yuanlin; Li, Tiandong; Liu, Haiyan; Ye, Hua; Shi, Jianxiang; Wang, Kaijuan; et al. (BMC public health, 2025)
Women of reproductive age (WRA), a key reproductive group, face mental health issues that impact both their own well-being and that of the next generation. However, research on the burden and trends of mental disorders among WRA remains limited. This study aimed to assess these on a global scale. The data from the Global Burden of Disease Study 2021 were utilized to analyze the age-standardized prevalence, age-standardized disability-adjusted life years (DALYs), and annual average percentage change (AAPC) of mental disorders among WRA from 1990 to 2021, examining variations by region, country, Socio-Demographic Index (SDI), and age group, along with DALYs attributable to risk factors. In 2021, there were 343.22 million cases of mental disorders among WRA, with the highest DALYs among all diseases. From 1990 to 2021, the global burden increased, particularly for anxiety and major depressive disorders during the COVID-19 pandemic. Significant variations were observed across regions and countries. The different age groups showed different distributions of subtypes. High SDI regions showed the highest burdens, and the AAPC and SDI exhibit different correlation patterns before and during the pandemic. The burden of bullying victimization rose both before and during the pandemic, while intimate partner violence significantly increased during the pandemic. The burden of mental disorders among WRA remained high from 1990 to 2021, exacerbated by the COVID-19 pandemic. Variations exist across regions, countries, age groups, and SDI, indicating a need for the development and adjustment of targeted interventions for WRA.